2017
DOI: 10.1177/0040517517712093
|View full text |Cite
|
Sign up to set email alerts
|

Development of superamphiphobic alumina nanofiber mats using trimethoxysilane with a short perfluoroalkyl chain

Abstract: To avoid the generation of hazardous, long-chain perfluoroalkyl carboxylic acids (CnF2n+1COOH, n ≥ 7), we develop relatively safer superamphiphobic alumina nanofiber mats. Our fabrication process focuses on two principles: lowering the surface energy using trimethoxy(1H, 1H, 2H, 2H-nonafluorohexyl)silane (C4F9CH2CH2Si(OCH3)3), which has short-chain perfluoroalkyls that are relatively safer than long-chain ones; and creating a high-roughness surface from electrospun alumina nanofibers with an average fiber diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 58 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…It is already known from previous studies with Al and other substrates that the decomposition of the organic groups forming hydrophilic functional groups after cooling occurs at temperatures higher than 350-400 °C. [71][72][73][74] The temperature tests using lower surface tension liquids than water showed that the coatings retained the oleophobicity, losing the superoleophobic properties (Figure 7a). At 550 °C, the surface became superoleophilic.…”
Section: Resultsmentioning
confidence: 99%
“…It is already known from previous studies with Al and other substrates that the decomposition of the organic groups forming hydrophilic functional groups after cooling occurs at temperatures higher than 350-400 °C. [71][72][73][74] The temperature tests using lower surface tension liquids than water showed that the coatings retained the oleophobicity, losing the superoleophobic properties (Figure 7a). At 550 °C, the surface became superoleophilic.…”
Section: Resultsmentioning
confidence: 99%